Application of Risk Management Science in Construction Project Learning: Cost Contingency Study in Malang Raya Housing - Fairuz Firyal Qonitah; Achfas Zacoeb; Retno Anggraini (Jurnal Penelitian Pendidikan IPA, 2025)
Housing projects are classified as complex and therefore require risk management analysis for economic and business sustainability for developers. Objective: To apply the risk management science approach to understand the dynamics of contingency costs in real housing construction projects and relate it to strengthening student competencies in construction project-based learning. Method: This research is descriptive because it aims to provide an overview of the facts in the field and the observed phenomena regarding the analysis of dominant contingency cost factors in housing development projects in Malang Raya. Data analysis: Data was obtained through interviews and questionnaires, then analyzed on several factors that influence cost contingencies in housing projects. Results: The dominant factors influencing contingency costs in housing development projects in Malang Raya consist of four main factors: Design, financial, human resources, and engineering. The contingency costs in housing development projects in Malang Raya generally range from 5% to 7.5% of the total project value. Contingency costs are higher in type 36 and 45 housing projects, especially with DP below 20%. Solutions that can be implemented to address risks that cause contingency costs to arise include preventive and corrective actions tailored to each risk factor.